Kajian Literatur mengenai Arah Pengembangan Ekonomi Kreatif di Indonesia Menuju Tahun 2030 - Rahmat Prayoga; Julius Christian Sitohang Julius Christian Sitohang (Cakrawala Akuntansi & Manajemen, 2023)
An in-depth look at the potential and challenges of the creative economy in 2030 and the strategies that need to be adopted to achieve a strong, creative, inclusive, and sustainable economic recovery, is presented by researchers compiled in the work of the book "Creative Economy 2030: Imagining and Delivering a Robust, Creative, Inclusive, and Sustainable Recovery" and added with other relevant sources. This paper examines the latest developments and innovations in the creative economy space, including the role of technology and digitalization in expanding the sector's reach and impact. This involves an in-depth analysis of how information and communication technologies, including artificial intelligence and blockchain, affect the way production and interaction with consumers in the creative sector. This book outlines the importance of the creative economy sector as one of the main pillars in spurring growth and innovation in the future. Through an interdisciplinary approach, the authors explore important aspects such as technology, art, culture, entrepreneurship, and innovation in shaping an economy driven by creativity.